Patterns of Alcohol Use in Early Adolescence Predict Problem Use at Age 16. - Heron, Jon; Macleod, John; Munafò, Marcus R.; Melotti, Roberto; Lewis, Glyn; Tilling, Kate; Hickman, Matthew (Alcohol & Alcoholism)
Aims: Teenagers in the UK report some of the highest rates of alcohol use in Europe. We identify patterns of alcohol use in early adolescence and relate these to hazardous and harmful alcohol use at age 16. Methods: In a UK birth cohort, we analysed repeated measures of alcohol use from age 13 to 15 in a sample of 7100 adolescents. Data on drinking frequency and typical consumption when drinking were modelled separately using a pair of latent class models. Classes of alcohol-use behaviour were contrasted across a range of risk factors and then to hazardous and harmful alcohol use as assessed using the Alcohol Use Disorders Identification Test scale at age 16. Results: Heterogeneity in drinking frequency and consumption could each be captured with three classes corresponding to low, medium and high levels. In total, 14.2% were classified as high-frequency and 8.9% as high consumption alcohol users. Socio-demographic factors, maternal substance use and the young persons' use of tobacco and cannabis were associated with class membership. At age 16, 29% were drinking hazardously and a further 5.6% were assessed as harmful drinkers. Young people in the high drinking frequency or consumption class had a 9-fold increased risk of reporting harmful drinking at age 16. Conclusions: By the age of 16, a substantial proportion of teenagers in this sample were drinking at levels that could be considered hazardous or harmful for an adult. Patterns of alcohol exposure in early adolescence were strongly associated with later alcohol use. Altering drinking patterns in middle adolescence has the potential to reduce harmful use in later adolescence.